A test procedure for uniformity on the Stiefel manifold based on projection - Iwashita, Toshiya; Klar, Bernhard; Amagai, Moe; Hashiguchi, Hiroki (Statistics & probability letters, 2017)
This paper proposes a new procedure to test uniformity on the Stiefel manifold. The theoretical analysis of the test procedure, and numerical experiments are conducted to illustrate the usage and the efficiencies through the power under alternative hypotheses.